Effectiveness of Chamomile Tea toward Sleep Quality Amount Autistic Children - Nuh Huda (Journal of Global Pharma Technology, 2016)
Introduction: Autistic children often experience sleep problems when compared to children in the general population. Difficulty in starting sleep or maintaining sleep occurs in about 10% to 20% of children aged 4-15 years; it can cause other problems such as behaviour disorders, cognitive, and hyperactivity. Consuming chamomile tea before going to sleep is believed to make the body's muscles relax and make the individual sleep faster. This study aims to analyze the effectiveness of chamomile tea on sleep quality in autistic children in Surabaya. Method: pre-experimental research with one group pre-post-test design. The population of 221 of autistic children with a sample of 66 respondents selected by simple random sampling. The instrument used a questionnaire sheet CSHQ (Children Sleep Habit Questionnaire), the independent variable in this study was the drinking of chamomile tea, the dependent variable was sleep quality, data were analyzed using the Wilcoxon Signed Test (α = 0.05). Results: after being given chamomile tea once every 2 days for 1 month it was found 54 respondents (81.8%) improved their sleep quality and 12 respondents (18.2%) had a stable sleep quality. Wilcoxon Signed Test results show the effectiveness of chamomile tea on sleep quality for children with autism p=0.0013. Conclusion: Chamomile tea has an active ingredient apigenin which will bind GABA in the brain to reduce excessive brain activity so that the body becomes calmer and more relaxed. So that chamomile tea can be consumed by children with autism to reduce sleep disorders.Keywords: Autistic children; Chamomile tea; Sleep quality.